Time for Break: Understanding Information Workers’ Sedentary Behavior Through a Break Prompting System - Luo, Yuhan; Lee, Bongshin; Wohn, Donghee Yvette; Rebar, Amanda L.; Conroy, David E.; Choe, Eun Kyoung (2018 ACM Conference on Human Factors in Computing Systems (CHI), 2018)
Extended periods of uninterrupted sedentary behavior are detrimental to long-term health. While prolonged sitting is prevalent among information workers, it is difficult for them to break prolonged sedentary behavior due to the nature of their work. This work aims to understand information workers’ intentions & practices around standing or moving breaks. We developed Time for Break, a break prompting system that enables people to set their desired work duration and prompts them to stand up or move. We conducted an exploratory field study (N = 25) with Time for Break to collect participants’ work & break intentions and behaviors for three weeks, followed by semistructured interviews. We examined rich contexts affecting participants’ receptiveness to standing or moving breaks, and identified how their habit strength and self-regulation are related to their break-taking intentions & practices. We discuss design implications for interventions to break up periods of prolonged sedentary behavior in workplaces.